CSRS/SCÉR (1976–2014) : une brève histoire de la Société canadienne d’études de la Renaissance / A Brief History of the Canadian Society for Renaissance Studies - Reeves, Margaret; Frappier, Louise (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
The Canadian Society for Renaissance Studies / Société canadienne d’études de la Renaissance (CSRS/SCÉR) was formed thirty-eight years ago at a Learned Societies meeting in Laval in May 1976. However, the society’s roots go even further back: the idea of forming such an association came from les seiziémistes, a group of Canadian francophone and anglophone scholars who began meeting in 1973, and who found common purpose in an intellectual community dedicated to the history, cultures, and literatures of the Renaissance. This brief history of the CSRS/SCÉR traces the beginnings of the society, its relations with other academic institutions, and the challenges it has faced since its inception. This account documents the means through which the CSRS/SCÉR has fulfilled its original goals by creating an intellectual community of Renaissance scholars that is bilingual, interdisciplinary, and national in scope.